Answer:
One pair of sunglasses is $70
Step-by-step explanation:
you miss3 out of 7 on a science quiz and 9 out of 23 on math quiz which quiz has a higher percent of correct answers
Science Quiz: 42.8571429%
Math Quiz: 39.1304348%
Take the amount of answers correct out of the total, divide it, and then multiply by 100. In this case, Science has a higher score.
The percentage of correct answers for the science quiz is 57.14%, while for the math quiz it's 60.87%. Therefore, the student had a higher percentage of correct answers on the math quiz.
Explanation:You determine the percentage of correct answers on each quiz by dividing the number of correct answers by the total number of questions on each quiz respectively.
For the science quiz, you answered 4 out of 7 questions correctly since you missed 3 out of 7. The percentage of correct answers for the science quiz is thus (4/7)*100 = 57.14%.
For the math quiz, you answered 14 out of 23 questions correctly since you missed 9 out of 23. The percentage of correct answers for the math quiz is thus (14/23)*100 = 60.87%.
Therefore, you had a higher percentage of correct answers on the math quiz than on the science quiz.
Learn more about Percentage of Correct Answers#SPJ2
Solve for x: 3x−8≤23 OR −4x+26≥6
Answer:
i am smort
Step-by-step explanation:
q
To solve the given system of inequalities, we can solve each inequality separately and then find the intersection of their solution sets. The solution set is x≤5.
Explanation:To solve the given inequality 3x-8≤23 or -4x+26≥6, we can solve each inequality separately and then find the intersection of their solution sets.
For the first inequality, 3x-8≤23, we add 8 to both sides and then divide by 3 to isolate x: 3x≤31, x≤31/3.
For the second inequality, -4x+26≥6, we subtract 26 from both sides and then divide by -4 to isolate x: -4x≥-20, x≤5.
Since x must satisfy both inequalities, the solution set is x≤5 and x≤31/3. Taking the smaller value, we have x≤5.
Solve the problem.
6. John bought three cups of root beer. Two of the cups were smalls and the last
was a large. All the cups together add up to 52 fl. oz. of root beer. If the large can hold 36 fl. oz.
of root beer, how much root beer can a small cup hold.
Answer:
the small cup of root beer can hold 8 fl. oz
Step-by-step explanation:
52-36=16
16/2=8
Each small cup holds 8 fl. oz. Together they hold 16 fl. oz. Plus 36 fl. oz. Which equals 52 fl. oz.
What is the solution to this equation x - 12 = - 4
Answer:
x = 8Step-by-step explanation:
x - 12 = -4 add 12 to both sides
x - 12 + 12 = -4 + 12
x = 8
mr morton sold bird houses to stores. he started the week with 60. he sold 10 to one store and divided the rest between 5 other stores. how many birdhouses did he sell to each of the other 5 stores?
Answer:
10
Step-by-step explanation:
Mr morton initially had 60 bird houses.
He sold 10 to one store.
So left number of birdhouses = 60 - 10 = 50.
He sold them equally to 5 stores,
So, each of them will get [tex]\frac{50}{5}[/tex] = 10 bird houses.
So,
He sold 10 birdhouses to each of the other 5 stores.
Which of the following problems can be solved by finding 4 divided by 2/3?
A. 4 people equally share 2/3 of a pizza. How much of the pizza does each person eat?
B. How many 2/3 cup servings of soup are in 4 cups of soup?
C. A pie recipe requires 2/3 pounds of apples. How many apples are needed for 4 pies?
D A family ate 2/3 of a 4 foot sandwich. How much did he they eat?
Arthur chose A as the correct answer. How did he get that answer?
Step-by-step explanation:
Arthur got because a pizza is shared by 4 people. however only
2/3 of the pizza is there so it is divided by the four people.
The correct option is b.
The correct problem that can be solved by calculating 4 divided by 2/3 is determining the number of 2/3 cup servings of soup in 4 cups. By understanding how division of fractions work, we can see that there are 6 such servings in 4 cups.
Explanation:The subject matter of the question is related to basic division and fractions. Specifically, it's asking about when we would need to find the result of 4 divided by 2/3. Given the answer choices, option B is the correct one. The question here is not about sharing a pizza or calculating the quantity of apples for pies, or the amount of sandwich eaten. It's rather about how many 2/3 cup servings fit within 4 cups of soup. When we do the division 4 ÷ 2/3, we're essentially figuring out how many 2/3s there are in 4. This concept can be a bit tricky because dividing by a fraction is equivalent to multiplying by its reciprocal. The reciprocal of 2/3 is 3/2, so 4 × 3/2 = 6. Hence, there are 6 servings of 2/3 cup soup in 4 cups.
Learn more about Division and Fractions here:https://brainly.com/question/17205173
#SPJ3
294 rounded to the nearest hundred
Answer:
300
Step-by-step explanation:
9 rounds it up
It took a car 5 days to travel 1459 miles. What was this car average speed in miles per hour ?
Answer:
12.1583333333 miles/hr.
Step-by-step explanation:
24 * 5 = 120 hrs
1459/120 = 12.1583333333
Answer:
12.158 miles/hour
Step-by-step explanation:
[tex]\frac{1459 miles}{5 days} = 291.8 miles/day\\\frac{291.8 miles}{1 day} x \frac{1 day}{24 hours} = 12.158 miles/hour[/tex]
One day, the high temperature was 84 degrees and the low temperature was 68 degrees. Write a compound inequality to represent the day’s temperatures
Answer:
x > 68 and x < 84
Step-by-step explanation:
Given: △AKM, KD ⊥ AM , AK = 6, KM = 10, m∠AKM = 93º Find: KD
The length of KD in triangle △AKM, with AK = 6 and KM = 10, and m∠AKM = 93° is 10, since KD is the height of a right triangle and KM is the hypotenuse.
The question asks to find the length of KD in triangle △AKM where KD is perpendicular to AM. Given AK = 6, KM = 10, and m∠AKM = 93º, we can solve for KD using trigonometric ratios.
Since KD ⊥ AM, we have a right triangle △KDM.
We know the hypotenuse KM and angle AKM, so we can use the sine function, where sin(AKM) = opposite/hypotenuse, to find the length of KD. The sine of angle AKM (which is slightly adjusted from 93º to 90º since we are looking for the height in a right triangle) gives us:
sin(90º) = KD/ KM
We know sin(90º) = 1 and KM = 10, so:
1 = KD / 10
Therefore, KD = 10.
What is y+2=⅞(x-3) in standard form?
Answer:
7x - 8y = 37
Explanation:
y+2 = ⅞(x-3) (distribute ⅞ -- x times 7/8, -3 times 7/8)
y+2 = ⅞x - 21/8 (subtract ⅞x from both sides)
y+2-⅞x = -21/8 (subtract 2 from both sides)
y-⅞x = -37/8 <--- result of -21/8 - 2
Multiply both sides by 8 to get ride of fractions
8y - 7x = -37 (rearrange)
-7x + 8y = -37
It's better to have a positive coefficient for x if you can. So multiply both sides by -1. That just means changing the sign of every term on both sides, you get
7x - 8y = 37
Thank you! Please do both
Answer:
my 12 inch pito that pito good
Shawn hikes up a mountain, back down the other side, then around the front of the mountain back to his truck. How far did he go if n = 5 and m = 6?
Answer:
The distance Shawn went is 40.
Step-by-step explanation:
Given:
N= 5 and M =6
Mountain hike = N = 5
Back down the other side = 2N+1 = 2×5 + 1 = 10 + 1 =11
From Mountain back to truck = 4M = 4×6 = 24
We need to find the total distance he went and can be calculate by adding Mountain hike with back down the other side and then from Mountain back to truck.
Total distance Shawn went = Mountain hike+ Back down the other side + From Mountain back to truck = 5 + 11 + 24 = 40
Hence Shawn went the distance of 40.
INEQUALITIES-PLEASE HELP! Tricia receives a $5 allowance every week. She also earns $6.50 for every hour that she baby-sits. Next week she wants to earn at least $21.25 to buy a present. Please write an inequality to math this equation.
Answer:
6.50x + 5 = 21.25 is the answer
Step-by-step explanation:
x=2.5
The inequality that represents Tricia's goal to earn at least $21.25 through her $5 allowance and $6.50 per hour from babysitting is E = 5 + 6.50h ≥ 21.25, where h represents the number of hours she babysits.
The student's question asks for an inequality to represent the situation where Tricia receives a $5 weekly allowance and earns $6.50 for each hour she babysits. The goal is to earn at least $21.25 to buy a present.
Let's denote the number of hours Tricia babysits as h. The inequality representing her total earnings E from both her allowance and babysitting will be:
E = 5 + 6.50h ≥ 21.25
This inequality implies that the sum of Tricia's weekly allowance ($5) and her babysitting earnings ($6.50 per hour multiplied by the number of hours h) should be at least $21.25.
alex grew 1 foot over the past year. He is now 6 feet tall
The area of a rectangle is 28 square meters. The length is 7 meters.
What is the width of the rectangle?
meters
To find the width of the rectangle, use the formula Width = Area ÷ Length. Given an area of 28 square meters and a length of 7 meters, the width is 4 meters.
The area of a rectangle is calculated using the formula:
Area = Length × Width
Given that the area is 28 square meters and the length is 7 meters, we can find the width by rearranging the formula:
Width = Area ÷ Length
Substitute the given values into the formula:
Width = 28 square meters ÷ 7 meters = 4 meters
Therefore, the width of the rectangle is 4 meters.
What is the answer to this
[tex] \frac{ {11}^{4} }{ {11}^{ - 1} } = {11}^{4} \times 11 = {11}^{5} = 161051[/tex]
[tex] {x}^{ - 1} = \frac{1}{x} [/tex]
[tex] {x}^{a} \times {x}^{b} = {x}^{a + b} [/tex]
Answer:
11⁵Step-by-step explanation:
[tex]\text{Use}\ \dfrac{a^n}{a^m}=a^{n-m}\\\\\dfrac{11^4}{11^{-1}}=11^{4-(-1)}=11^{4+1}=11^5[/tex]
A fruit company delivers its fruit in two types of boxes: large and small. A delivery of 2 large boxes and 6 small boxes has a total weight of 128 kilograms. A delivery of 5 large boxes and 3 small boxes has a total weight of 137 kilograms. How much does each type of box weigh?
The weight of a large box is 18.25 kilograms and the weight of a small box is 15.25 kilograms.
Explanation:Let's use a system of equations to solve this problem. Let's assume the weight of a large box is 'x' and the weight of a small box is 'y'. Based on the given information, we can set up the following equations:
2x + 6y = 128 (equation 1)5x + 3y = 137 (equation 2)Now, we can solve this system of equations to find 'x' (the weight of a large box) and 'y' (the weight of a small box).
We can start by multiplying equation 1 by 5 and equation 2 by 2 to eliminate 'x':
10x + 30y = 640 (equation 3)10x + 6y = 274 (equation 4)Subtracting equation 4 from equation 3:
24y = 366
Simplifying:
y = 15.25
Substituting the value of 'y' back into equation 1 or 2, we can solve for 'x':
2x + 6(15.25) = 1282x + 91.5 = 1282x = 128 - 91.52x = 36.5x = 18.25Therefore, a large box weighs 18.25 kilograms and a small box weighs 15.25 kilograms.
Learn more about Solving systems of equations here:https://brainly.com/question/29050831
#SPJ3
A wooden beam is left parenthesis 6 y squared plus 5 y plus 1 right parenthesis6y2+5y+1 meters long. If a piece of length left parenthesis y squared minus 12 right parenthesisy2−12 meters is cut off, express the length of the remaining piece of beam as a polynomial in y.
Answer:
5y² + 5y - 11
Step-by-step explanation:
The length of a wooden beam is as a function of y
L(y) = 6y² + 5y + 1
and a piece of length y² - 12 is cut off the remaining piece is
6y² + 5y + 1 - y² - 12 = 5y² + 5y - 11
To find the remaining length of the wooden beam, subtract the length of the cut-off piece from the original polynomial. Simplify the expression to get the final answer: 5y² + 5y + 13 meters. This represents the remaining length of the beam.
Finding the Remaining Length of the Wooden Beam:
We start with the original length of the wooden beam given by the polynomial 6y² + 5y + 1 meters.
We need to subtract the length of the piece that was cut off, which is given by the polynomial y² - 12 meters.
First, write down the original length of the beam:
6y² + 5y + 1
Next, identify the length of the piece cut off:
y² - 12
Subtract the second polynomial from the first:
(6y² + 5y + 1) - (y² - 12)
Simplify the expression by combining like terms:
6y² - y² = 5y²
5y remains unchanged.
1 - (-12) = 1 + 12 = 13
So, the remaining length of the beam is:
5y² + 5y + 13
The remaining length of the wooden beam, expressed as a polynomial in y, is 5y² + 5y + 13 meters.
Which expression is equivalent to the expression (-18) - 64n?
A -2(9 - 32n)
B 2(9 - 32n)
C -2(9 + 32n)
D 2(9 + 32n)
Answer:
C) -2(9+32n)
Step-by-step explanation:
(-18)-64n=-18-64n
---------------------------
A) -2(9-32n)=-18+64n
B) 2(9-32n)=18-64n
C) -2(9+32n)=-18-64n
D) 2(9+32n)=18+64n
-----------------------------------
The answer is C.
if my grade is a 49.1 F and i get 90 points on a test what will my grade go to
Answer:
A I think
Step-by-step explanation:
49.1+ 90
Answer:
C
Step-by-step explanation:
Find the average of the two test scores.
(49.1 + 90)/2
139.1/2
69.55 ⇒ which is grade C
use the method of completing the square to solve y²+y-7=0
Answer:
y = sqrt(29)/2 - 1/2 or y = -1/2 - sqrt(29)/2
Step-by-step explanation:
Solve for y:
y^2 + y - 7 = 0
Add 7 to both sides:
y^2 + y = 7
Add 1/4 to both sides:
y^2 + y + 1/4 = 29/4
Write the left hand side as a square:
(y + 1/2)^2 = 29/4
Take the square root of both sides:
y + 1/2 = sqrt(29)/2 or y + 1/2 = -sqrt(29)/2
Subtract 1/2 from both sides:
y = sqrt(29)/2 - 1/2 or y + 1/2 = -sqrt(29)/2
Subtract 1/2 from both sides:
Answer: y = sqrt(29)/2 - 1/2 or y = -1/2 - sqrt(29)/2
Answer:
y=sqrt(29)/2-1/2, -sqrt(29)/2-1/2
Step-by-step explanation:
y^2+y-7=0
completing the square,
(b/2)^2=(1/2)^2=1/4
(y+1/2)^2=7+1/4
(y+1/2)^2=28/4+1/4
(y+1/2)^2=29/4
y+1/2=sqrt(29/4)
y=sqrt(29/4)-1/2
y=sqrt(29)/2-1/2
y=-sqrt(29)/2-1/2
Over the course of a year, a company goes from 115 employees to 124 employees.
Use the drop-down menus to build an equation that could be used to find the percent change, p, in the number of employees
Answer:
on the top is 124 - 115 whille in the bottom is 115
Step-by-step explanation:
To calculate the percent change in the number of employees, use the formula (Change in Quantity / Original Quantity) × 100. The original number of employees is 115, and it increased to 124, resulting in a change of 9. The percent change is approximately 7.83%.
Explanation:To find the percent change in the number of employees, you can use the following formula:
Percent Change (p) = (Change in Quantity / Original Quantity) × 100
In this case, the Original Quantity is the number of employees at the start of the year (115) and the Change in Quantity is the difference between the number at the end of the year (124) and the number at the start of the year (115).
So, we calculate Change in Quantity as 124 - 115 = 9.
Now, using the formula:
p = (9 / 115) × 100
Calculating this gives us the percentage change:
p = (9 / 115) × 100 ≈ 7.83%
The percent change in the number of employees is approximately 7.83%.
Learn more about Percent Change here:https://brainly.com/question/17968508
#SPJ3
2kilogram convert into g
Answer:
The answer is 2000 g
Step-by-step explanation:
We use the following equivalence:
1 kg-------1000g
2kg----- X = (2kgx1000g)/1kg= 2000g
Samantha buys candy bars for $0.75 each and increases the price by 40% to sell at the concession stand. Which represents the amount of the price increase?
(A) $ 0.30
(B) $ 0.40
(C) $ 0.50
(D) $ 0.60
Answer:
Try to include yes 0.30
Step-by-step explanation:
That is because we have to check the top and the bottom the add and multiply
Answer:
a.) $0.30 cents is the answer
Step-by-step explanation:
.75 • .4
What’s 333x333 please I need to know
Answer:
110889
Step-by-step explanation:
Answer:
110,889 is the answer dude..
Factor −1/2 out of −1/2x+6.
The factored expression is
Final answer:
To factor −1/2 out of −1/2x+6, we identify the common factor, divide each term by −1/2, and write the expression as −1/2 times the simplified expression. The result is −1/2(x − 12).
Explanation:
To factor −1/2 out of −1/2x+6, we can think of pulling out the −1/2 as a common factor from both terms in the expression. Here's a step-by-step breakdown:
Identify the common factor in both terms. In this case, the common factor is −1/2.Divide each term by −1/2 (which is the same as multiplying by −2).Write the original expression as the product of the common factor and the simplified expression.Applying these steps, we get:
−1/2x divided by −1/2 equals x.6 divided by −1/2 equals −12.The factored expression is then −1/2(x − 12).So, −1/2x+6 factored with −1/2 taken out is −1/2(x − 12).
The football team scored 28 points in the
first game. 35 points in their second game,
and 17 points in the third game About how
many points were scored in all three
games?
Answer:
80 points
Step-by-step explanation:
28+35=63.
63+17=80.
Hope this is addition.
That simple
By adding the points scored in each game, we find that the football team scored a total of 80 points in all three games.
Explanation:To find the total number of points the football team scored in all three games, we simply have to add the points scored in each game together. So, in the first game the team scored 28 points, in the second game they scored 35 points, and in the third game they scored 17 points. If we add these scores together (28 + 35 + 17), we get a total of 80 points. Therefore, the football team scored 80 points in all three games.
Learn more about Adding here:https://brainly.com/question/32114123
#SPJ11
2. One of the most common mutagens in
our environment, that we are exposed
to everyday we are outside in the
sunlight, is
O UV radiation
infrared radiation
Answer:
Ultraviolet (UV) radiation.
Step-by-step explanation:
Mutagen is part of genetics, it is chemical or physical agent which are present in atmosphere and causes changes or mutation in the genetic materials i.e. in DNA (these changes can be permanent as well). Example of mutagen are radioactive substances, ultraviolet radiation, etc.
UV radiation is an electromagnetic radiation which is present in sunlight. It is a strong mutagen which is when absorbed by DNA can cause extreme damage, for example, uncontrolled division of skin cell can cause skin cancer, that's the reason why UV radiation is the most common mutagen to which we are exposed to when we are outside in the sunlight.
What number would x be for 2x+1/3 and 2x be the same equation
Answer:
No solution.
Step-by-step explanation:
2x+1/3=2x
1/3=2x-2x
1/3=0
no solution